The relationship between static and dynamic occlusion based on the relationship between anterior and posterior teeth and the occlusion scheme in dentistry students - Riri Harliani SIHOTANG; Ariayani ARIYANI (Journal of Syiah Kuala Dentistry Society, 2022)
Occlusion is important in the mastication process. Tooth occlusion is generally classified into static occlusion and dynamic occlusion. Static occlusion is visible through the relation of both anterior and posterior teeth. Incisor relationships were classified according to the British Standard Institution (BSI), while Angle was classified based on the relationship of the first molars in permanent teeth. The classification of occlusion according to Angle and BSI is based on the description of the shape of the arch, tooth position, and tooth contact in the intercuspal position. This study aims to determine the distribution of static occlusion based on the relationship between anterior and posterior teeth as well as dynamic occlusion distribution based on the occlusion scheme and the relationship between static and dynamic occlusion in students of the Faculty of Dentistry, University of North Sumatra. It is a descriptive-analytic with a cross-sectional study design. The sample consisted of 100 students with a complete set of teeth. Each sample was examined using shim stock and articulation paper. The results of statistical using the chisquare test showed a significant relationship between static and dynamic occlusion based on the relationship between anterior teeth (p 0.05) and the relationship between posterior teeth (p 0.05).KEYWORDS: occlusion, static occlusion, dynamic occlusion